Strengthening The Competency- And Performance-Based Performance Allowance System Through Work Motivation Mediation In The Context Of Local Bureaucratic Reform - Sartika Sari; Sari Sakarina; Dian Yulistarini (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2026)
Bureaucratic reform requires strengthening the performance allowance system, which should not only be based on formal achievements but also consider the competence and work motivation of civil servants. This study aims to analyse the influence of competence and performance on performance allowances, with work motivation as a mediating variable in the General Affairs and Equipment Bureau of the South Sumatra Provincial Secretariat. The study uses a quantitative approach with the Structural Equation Modelling–Partial Least Square (SEM-PLS) method. The research sample consisted of 112 civil servants determined through saturated sampling techniques. The analysis results show that competence and performance have a positive and significant effect on work motivation and performance allowances. Work motivation was found to partially mediate the relationship between competence and performance allowances (VAF = 25.2%) and between performance and performance allowances (VAF = 21.7%). The coefficient of determination values indicate the model's strong predictive power, with R² of 0.941 for work motivation and 0.782 for performance allowances. These findings confirm that the effectiveness of the performance allowance system in the public sector requires strengthening competencies and managing work motivation as internal psychological mechanisms. This study provides theoretical contributions to the development of performance-based remuneration models and practical implications for the formulation of human resource management policies in the local bureaucracy.